Optimizing History Learning Through Integration Of Digital Resources In High School - Astrini Eka Putri (Jurnal Scientia, 2024)
The use of digital technology in history learning in high school can improve the quality of learning and student interest. The integration of digital sources such as e-books, documentary videos, augmented reality (AR), and virtual reality (VR) makes learning more engaging, interactive, and relevant. This study aims to identify effective strategies, challenges, and impacts of using digital resources in history learning in high school. The integration of social media and digital resources can increase student engagement, enrich their understanding, and improve learning achievement. However, challenges such as technical limitations, content quality, and teacher skills need to be addressed. Investments in technology infrastructure, teacher training, and effective curriculum development are critical to addressing these challenges. A planned and systematic strategy is required for the development of digital learning materials and the utilization of online learning platforms. The use of AR and VR technology can enhance students' learning experiences, while history-based educational games can increase student engagement and motivation. Thus, history learning can be more engaging, interactive, and effective, having a positive impact on student understanding and achievement.